2014
DOI: 10.1255/tosf.23
|View full text |Cite
|
Sign up to set email alerts
|

Illusory reconciliation: compensation of manual sampling errors

Abstract: In the mining industry, reconciliation can be defined as the practice of comparing the tonnage and average grade of ore predicted by the geological models with the tonnage and grade generated by the processing or metallurgical plant. This practice is of increasing importance, since, if correctly executed, it allows the reliability of short-term planning to be improved and the mining and processing operations to be optimised. However, the usefulness of reconciliation relies strongly on the quality of the input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The previous work 3 proved that this drilling rig is not able to recover all the material from the hole, especially the coarse and consequently lower grade material. Thus, the fragments sent to the surface piles (finer fragments) are richer than the original lot (all fragments composing the drill hole: fines, medium and coarse).…”
Section: Earlier Sampling Proceduresmentioning
confidence: 95%
See 1 more Smart Citation
“…The previous work 3 proved that this drilling rig is not able to recover all the material from the hole, especially the coarse and consequently lower grade material. Thus, the fragments sent to the surface piles (finer fragments) are richer than the original lot (all fragments composing the drill hole: fines, medium and coarse).…”
Section: Earlier Sampling Proceduresmentioning
confidence: 95%
“…In 2013 3 , the authors presented the results of a sampling campaign in the same mine, which demonstrated the tendency of the Furukawa to overestimate both gold and copper grades, especially due to poor recovery (only 80%) coupled with segregation between fines and coarse material. Therefore, a reverse circulation (RC) drilling rig with automatic sampling system (recovery of up to 99%) was recommended, in order to minimise the errors generated by manual sampling, such as the increment delimitation error, the increment extraction error, the increment weighting error and the grouping and segregation error (IDE, IEE, IWE, GSE).…”
mentioning
confidence: 99%